Avaliação do papel das citocinas interleucina 32 e interleucina 15 em macrófagos humanos primários infectados com Leishmania (Viannia) braziliensis - Silva, Lucas Luiz de Lima (2016)
American Tegumentary Leishmaniasis (ATL) is a disease caused by Leishmania protozoan, belonging to the subgenus Viannia and Leishmania. In Brazil, the most common and prevalent species is L. (V.) braziliensis. In patients with ATL, it was detected the expression of interleukin 32 (IL-32) in skin or mucosal lesions caused by L. Viannia spp. However, the role of IL-32 on ATL is still unclear. It has been shown that IL-15 induces IL-32 and also IL-15 leads to L. infantum control. This study aimed to investigate the effects of IL-32 and IL-15 in the production of cytokines and microbicidal activity of primary human macrophages infected with L. (V.) braziliensis. For this, human peripheral blood monocytes were derived into macrophages and infected with metacyclic forms of L. (V.) braziliensis; evaluation of the infection index (4 h, phagocytosis, 48 h, microbicidal activity) in the absence or presence of rIL-32, rIL-15 or gamma interferon (rIFN) and lipopolysaccharide (LPS); in culture supernatants, IL-32, tumor necrosis factor (TNF) and IL-10 were measured by enzime-linked immunoassay. The addition of rIL-32 to macrophages did not significantly altered phagocytosis of the parasites or microbicidal activity of macrophages. Classical activation of macrophages with rIFN plus LPS decreased the infection index. rIL-32 em high concentration (200 ng/mL) was able to induce TNF in uninfected or infected macrophages, and IL-10 was not induced. Parasites induced lower amounts of intracellular IL-32 as well as rIFN0.1 ng / ml), but there was a synergism between the activation signals provided by the parasites and rIFN (0.1 ng / ml). In the opposite, rIFN in higher concentration (10 ng/mL) induced higher amounts of IL-32, but its activity was partially inhibited by parasites. The rIL-15 was able to induce IL- 32 and TNF in macrophages, but not IL-10 in both non-infected or infected macrophages. The rIL-15 also decreased phagocytosis of parasites by macrophages and increased the microbicidal activity of these cells. The data suggest that IL-15 induces IL-32 and TNF which can contribute to control of the infection. To evaluate the leishmanicidal mechanism pathways induced by IL-15 and IL-32 can help in the development of new therapies for the control of ATL.